(untitled) (The Pakistan Development Review, 1976)
Concerted efforts are being made at micro as well as macro levels in Pakistan to increase farm production and raise productivity in the agricultural sector. For diagnostic purposes and for formulation of general guidelines for an intelligent decision making, at micro and macro levels, it is important to identify and quantify the contribution of various factor inputs, especially of those factors whose supplies can be more easily changed in the short run. Satisfactory quantitative estimates of resource productivity in the pro¬duction of major crops in Pakistan are generally not available. Except for a few studies carried out on wheat [2], not much is known about the contribution of various factor inputs, such as farm labour, fertilizers, etc., to the final output. The main objective of this paper is to estimate and analyse the resource pro¬ductivity of various factor inputs obtaining in the Punjab’s agriculture. The estimates are derived from production function analysis performed on the major crops of the province, i.e. Mexi-Pak and local wheat, Basmati rice, IRRI rice, Jhonna rice, maize (corn), cotton and sugarcane. The marginal product¬ivities of various farm inputs in the production of various crops are computed from the estimated production functions.